2020
DOI: 10.1016/j.euroecorev.2020.103512
|View full text |Cite
|
Sign up to set email alerts
|

Becoming sensitive: Males’ risk and time preferences after the 2008 financial crisis

Abstract: This paper presents evidence suggesting men's (but not women's) risk and time preferences have systematically become sensitive to local economic conditions since the 2008 financial crisis. Studying longitudinal, nationally representative data for 22,579 Australian-based respondents in up to 11 surveys from 2002-2015, men respond with increased risk aversion and impatience to a rise in their region's unemployment rate-but only since 2008. We find no such relationship for women or before the crisis. This conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 89 publications
1
6
0
1
Order By: Relevance
“…This regulation aims to stimulate company tax relief, with the intention of potentially leading to employee terminations. The rise in poverty rates in Indonesia during the 2008 crisis (Herawati and Gustan, 2020) is indicative of a significant concern, similar to the situation observed in Australia and other countries (Jetter et al, 2020).…”
Section: Introductionsupporting
confidence: 57%
“…This regulation aims to stimulate company tax relief, with the intention of potentially leading to employee terminations. The rise in poverty rates in Indonesia during the 2008 crisis (Herawati and Gustan, 2020) is indicative of a significant concern, similar to the situation observed in Australia and other countries (Jetter et al, 2020).…”
Section: Introductionsupporting
confidence: 57%
“…The results are not sensitive to the single time dummy variable. The advantage of ‘PostGFC’ is that it accounts for changes in labour supply that may relate to changed preferences following the 2008 Global Financial Crisis (Jetter et al, 2020). It may also capture changed preferences following the enactment of the Paid Parental Leave Act 2010 in Australia (which came into effect in 2011) (Bass, 2020; Baird and Whitehouse, 2012).…”
Section: Datamentioning
confidence: 99%
“…Fear constitutes a potential mechanism for an increase in risk aversion (Guiso et al 2018 ). The study of Jetter et al ( 2020 ) found that men became more sensitive to unemployment rates and there was an increase in their risk aversion with increasing unemployment rates after the GFC. In Hoffmann et al ( 2013 ), risk perceptions during the times of turmoil in the GFC period substantially increased, while risk tolerances decreased.…”
Section: Individuals’ Risk-taking Behavior and Investment Decisionsmentioning
confidence: 99%